Hubungan Antara Hiperglikemi dengan Kejadian Infark Serebri pada Pemeriksaan Multi Slice CT-scan Kepala Tanpa Kontras di RSUD Dr. Moewardi - Siska Dewi Agustina; . Widiastuti; Jarot Subandono (Nexus Kedokteran Klinik, 2014)
Background: In recent year, numerous studies reported that stress hyperglycemia has been shown to be a risk factor for neurocardiovascular disease, with high risk of dying from coronary disease such as stroke. Stroke is the third leading cause of death in the world, with a high prevalence of death in low-and middle-income countries. Hyperglycemia has been associated with increased cerebral lactate resulting in local brain tissue acidosis. It worsens mitochondrial function in the penumbra, the moderately ischemic tissue of the brain. CT-scans are considered sufficiently sensitive for detecting mass lesions, such as a brain mass or abscess, as well as detecting acute hemorrhage. The aim of this study is to determine the relationship between hyperglycemia with cerebral infarction in non contrast multi slice head CT-scan. Methods: This was an observational cross sectional study. A total of 70 subjects were selected by fixed disease sampling, they were patients who have been perfomed non contrast multi slice head CT-scan in Dr. Moewardi Hospital. Data were collected from the report result of non contrast multi slice head CT-scan and the result of glucose blood level on patiensmedical record.Data analysis used chi square models and were processed with Statistical Product and Service Solutions (SPSS) 17.00 for Windows. Results: This study showed a positive association and statistically significant between hyperglycemia with cerebral infarction (?2 = 8,123; p<0.05) with moderate correlation strength. The result of OR (Odds Ratio) for cerebral infarction is 4,667 (CI 95% = 1,557 13.983). Confounding factor, e.g blood pressure and age have been controlled. Conclusions: There is a significance association between hyperglycemia with cerebral infarction in multi slice head CT-scan noncontrast at Dr Moewardi Hospital . Keywords: Hyperglycemia, cerebral infarction, head CT-scan without contrast